Vulnerability assessment and construction recommendations of local houses in the cyclone prone coastal areas of Bangladesh. (March 2017) - Alam, M.R.; Kaish, A.B.M.A.; Zain, M.F.M.; Dev, S.K.; Mahzabin, M.S.
Abstract: Bangladesh has approximately 710 km long coastline at its southern part. This huge coastal region is very much prone to tidal surge and cyclones; and approximately in every 5 years devastating cyclonic storm hits these coastal areas. The entire coastline suffers serious damage of locally built traditional or non-engineered houses in almost every year. Therefore, this study investigates a proper wind-resistant housing concept, so that people can build houses which are structurally strong to resist the high speed winds and as well be within their affordable financial limits. In order to carry out this study, existing housing data in the extreme wind-swept coastal areas of Chittagong, Cox-bazar and Patuakhali districts of Bangladesh was collected and analyzed to categorize different housing patterns. Some houses were found very poor in condition from the construction point of view and were not recommended for further strengthening. Some houses were found good in condition but had been constructed without following any engineering practices. These types of houses were considered for further strengthening to resist high speed winds that are prevalent in the coastal areas of Bangladesh. A specific pattern of house was analyzed using finite element software ANSYS 11.0. Thereafter, different types of strengthening techniques were applied and analyzed them for obtaining stress and deflection data. Results show that the deflections reduced by 95% when simple strengthening techniques (adding tie and bracing at some important points) were applied to the existing houses. This article also provides some guidelines for construction of houses in cyclone-prone areas. Highlights: Proper high speed wind-resistant housing concept is investigated. Surveyed existing houses in the coastal areas of Bangladesh. Analyze the resistance of a specific type of house against high speed wind. Recommends some strengthening techniques for houses in the coastal areas.